Aerobic versus anaerobic training for success in various athletic events - Shepard, R. J. (Canadian Journal of Applied Sport Sciences, 1978)
CLASSIFICATION OF ACTIVITIES BASED ON PERFORMANCE DURATION: - Single Maximum Contraction Event - Very Brief Events (less than 10 seconds) - Brief Events (10 to 60 seconds) - Sustained Events (60 seconds to 60 minutes) - Prolonged Events (60 minutes and longer) With the specific features four these group concerning physiology and training.